Analysis of clinical risk factors for metabolic bone disease of prematurity - Liu, Xiumin; Wang, Ling; Qian, Min (Frontiers in Pediatrics, 2024)
Objective To analyze clinical data related to preterm infants and identify risk factors for metabolic bone disease of prematurity (MBDP). Methods This study involved 856 newborns with a gestational age of less than 37 weeks or a weight of less than 1,500g at the Second Hospital of Jilin University. Multifactorial analysis was performed using logistic regression models to explore the risk factors for MBDP. Linear regression was used to investigate the factors affecting the time of alkaline phosphatase (ALP) exceedance and the peak value of ALP in the MBDP group. Results In the MBDP group, ALP excesses occurred in preterm infants at an average of 39.33 days after birth, and the mean value of peak ALP was 691.41 IU/L. Parenteral nutrition and the application of assisted ventilation were independent risk factors for MBDP, with ORs of 1.02 and 1.03 respectively. Gestational age was found to be a protective factor for earlier time of onset of ALP exceedance (β=2.24,) and the increase in the peak value of ALP (β=-16.30). Conclusion Parenteral nutrition and the application of assisted ventilation are independent risk factors for MBDP. Gestational age is a major factor influencing the time of onset of ALP exceedance and the peak value of ALP in infants with MBDP.